Right to Property and Maintenance of Illegitimate Children in India: Examining the Ownership Rights and Maintenance of Illegitimate Children in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Illegitimate children's ownership rights over their parents' property. Illegitimate children's rightsto inherit their parents' property are determined by personal laws of the parents because there is nospecific legislation defining what constitutes an illegitimate kid. In the past, illegitimate offspring were notaccorded the same privileges as legitimate ones under Hindu law however, in today's dynamic culture,this is no longer the case. Since neither Muslim nor Christian law acknowledges the word illegitimate,the unborn child has no legal recourse. The law may remain unchanged, but it is the judiciary's job toadapt the law to the changing requirements of society. Section 125 of the CrPC, which supersedespersonal laws and mandates the maintenance of illegitimate offspring, is mentioned in the studyexamining the property rights of such children, A uniform set of rules governing illegitimate children'sownership of their parents' property is urgently required. When a child is innocent, the burning must becarried by the child, which has to be changed.